2021
DOI: 10.3389/fmed.2021.655871
|View full text |Cite
|
Sign up to set email alerts
|

A Nephrologist Perspective on Obesity: From Kidney Injury to Clinical Management

Abstract: Obesity is one of the epidemics of our era. Its prevalence is higher than 30% in the U.S. and it is estimated to increase by 50% in 2030. Obesity is associated with a higher risk of all-cause mortality and it is known to be a cause of chronic kidney disease (CKD). Typically, obesity-related glomerulopathy (ORG) is ascribed to renal hemodynamic changes that lead to hyperfiltration, albuminuria and, finally, impairment in glomerular filtration rate due to glomerulosclerosis. Though not only hemodynamics are resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 127 publications
1
32
0
5
Order By: Relevance
“…Notably, risk of DCGL was more exaggerated than that of all-cause graft loss in both NOD-OR and OD-OR. This finding is in keeping with other studies which have shown a comparable mortality risk between obese recipients and those with a normal BMI ( 4 , 6 , 12 ). While this appears counter-intuitive given the greater burden of co-morbidities in obese individuals and the association of obesity with mortality in the general population ( 40 ), there are a number of possible explanations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notably, risk of DCGL was more exaggerated than that of all-cause graft loss in both NOD-OR and OD-OR. This finding is in keeping with other studies which have shown a comparable mortality risk between obese recipients and those with a normal BMI ( 4 , 6 , 12 ). While this appears counter-intuitive given the greater burden of co-morbidities in obese individuals and the association of obesity with mortality in the general population ( 40 ), there are a number of possible explanations.…”
Section: Discussionsupporting
confidence: 93%
“…The global rise in obesity is reflected in the kidney transplant population, with the proportion of recipients with a body mass index (BMI) in excess of 30 kg/m 2 doubling every 15 years ( 3 ). As obesity rates increase in the general population, the number of obese transplant candidates and kidney donors, both living and deceased, is also expected to increase ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…8,22 Finally, it is also important to highlight the impact of hypertension or T2DM (both highly prevalent in obesity) on renal outcomes in ORG. 23 These two conditions contribute to hyperfiltration and glomerular hypertension due to increased renal plasma flow and impaired autoregulatory capacity and may amplify kidney damage in patients with ORG. 23…”
Section: Hemodynamic Changes and Hyperfiltrationmentioning
confidence: 99%
“… 23 These two conditions contribute to hyperfiltration and glomerular hypertension due to increased renal plasma flow and impaired autoregulatory capacity and may amplify kidney damage in patients with ORG. 23 …”
Section: Org Pathophysiologymentioning
confidence: 99%
“…In the group of obese patients, the standard error was smaller if a correction for actual body weight was used, which was a very important factor for assessing creatinine clearance. [ 16 17 ] Luke et al . compared inulin clearance, creatinine clearance with five formulas for assessing creatinine clearance and glomerular filtration, which use gender, age, body height, body weight.…”
Section: Introductionmentioning
confidence: 99%